Tools and means to understand different TVET models in developing countries : an approach to the epistemological opening up of international TVET in development cooperation - Wolf, Stefan [Verfasser] (My University, 2020)
"The topic of my text is a critical reflection on concepts used in international comparative technical vocational education and training (TVET) research to analyse initial and continuing vocational training in other countries. Specifically, when cooperating on developing and transferring TVET policies, the challenge is to quickly understand the diverse concepts of skills development and TVET in the respective partner countries. Firstly, we must consider the varieties of skills development and TVET models; secondly, we must regard them in their respective contexts. Therefore, I will offer a brief presentation of typologies used in development cooperation to break down the characteristics of vocational education and training in different countries. The main emphasis, however, lies on the heuristic analysis concept of work culture in the context of existing qualification and skills development models. A case study of its use as a heuristic will be critically discussed, the central questions being the scope, limitations, problems and strengths of this tool. The conclusion is that the analysis concept is still too demanding for routine use in development cooperation and needs to be revised by means of a detailed questionnaire and a work guide." (author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; I 2.3 Außereuropäische Regionen; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Arbeitsmarkttheorie; Kompetenzmodell; Kompetenzentwicklung; Arbeitskultur; Entwicklungsländer